2021
DOI: 10.3389/fphys.2020.625974
|View full text |Cite
|
Sign up to set email alerts
|

The Heart of the Alzheimer's: A Mindful View of Heart Disease

Abstract: Purpose of Review: This review summarizes the current evidence for the involvement of proteotoxicity and protein quality control systems defects in diseases of the central nervous and cardiovascular systems. Specifically, it presents the commonalities between the pathophysiology of protein misfolding diseases in the heart and the brain.Recent Findings: The involvement of protein homeostasis dysfunction has been for long time investigated and accepted as one of the leading pathophysiological causes of neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…Based on this hypothesis, the cardiac pulsation in AD patients may be altered 10 and fAPF is able to reveal it. Recent findings showed that heart failure may co-occur in AD patients with the prevalence of one third of cases 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on this hypothesis, the cardiac pulsation in AD patients may be altered 10 and fAPF is able to reveal it. Recent findings showed that heart failure may co-occur in AD patients with the prevalence of one third of cases 11 .…”
Section: Resultsmentioning
confidence: 99%
“…7b ). Accumulation of protein aggregates marked by hyperphosphorylation of Tau is a well-known hallmark of Alzheimer’s disease, but it has also been linked to the pathogenesis of heart disease 37 . Using an antibody recognizing phospho-Tau S385 in mice, corresponding to S396 in human, we observed lower levels of phosphorylated Tau in hearts lacking ErbB2 and/or ERRα, suggesting that this proteotoxic stress is not an underlying cause of the observed DCM in these mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 In the heart, proteotoxicity is now recognized to promote ventricular dysfunction and cardiomyopathy. 3,4 In addition, amyloidosis predictably develops in the human atrium with aging, exceeding 90% in the ninth decade of life, and its presence is linked to AF. 5 In this senile form of amyloid, natriuretic peptides have been implicated: atrial deposits are uniformly immunoreactive for ANP (atrial natriuretic peptide), while BNP (B-type natriuretic peptide) has also been detected.…”
mentioning
confidence: 99%